Anthocyanin Retention of Cranberry (Vaccinium macrocarpon) Juice Subjected to Different Nanofiltration Conditions. (30th August 2017) - Ah-Hen, Kong; Costa, Marcia; Poo, Susan; Lemus-Mondaca, Roberto
Abstract : The aim of this work was to evaluate the retention of anthocyanin during a nanofiltration process of cranberry juice. Nanofiltration membranes, HC-50P DDS with an effective area of 0.36 m 2 in a plate/frame nanofilter system, DDS Lab Module, were used for the experiments. Juice feed flow rate varied from 1.0 to 12.0 L min −1 at transmembrane pressures between 20 and 40 bar (2026 and 4052 kPa). Permeate flux reached a maximum value of 41.3 L h −1 m −2 at a pressure of 40 bar and a feed rate of 12 L min −1, showing a direct dependency on these two parameters. Retention coefficients of anthocyanin of 0.94 to 0.99 corresponding to percentage recovery between 93 and 99% were obtained. Total anthocyanin content increased to values between 237 and 287 mg L −1 from original concentration of 82 to 97 mg L −1 in feed solution. Total soluble solids were also retained on the nanofilter. Both anthocyanin retentate and permeate obtained by nanofiltration could be potential functional ingredients for the food and nutraceutical industry.